Costly signaling and the handicap principle in hunter‐gatherer research: A critical review. Issue 3 (6th March 2019) - Stibbard‐Hawkes, Duncan N. E.
Abstract: It has been argued that men's hunting in many forager groups is not, primarily, a means of family provisioning but is a costly way of signaling otherwise cryptic qualities related to hunting ability. Much literature concerning the signaling value of hunting draws links to Zahavi's handicap principle and the costly signaling literature in zoology. However, although nominally grounded in the same theoretical paradigm, these literatures have evolved separately. Here I review honest signaling theory in both hunter‐gatherer studies and zoology and highlight three issues with the costly signaling literature in hunter‐gather studies: (a) an overemphasis on the demonstration of realized costs, which are neither necessary nor sufficient to diagnose costly signaling; (b) a lack of clear predictions about what specific qualities hunting actually signals; and (c) an insufficient focus on the broadcast effectiveness of hunting and its value as a heuristics for signal recipients. Rather than signaling hunting prowess, hunting might instead facilitate reputation‐building.